2013
DOI: 10.1007/s11629-013-2652-2
|View full text |Cite
|
Sign up to set email alerts
|

Woody species diversity and forest structure from lowland to montane forest in Hyrcanian forest ecoregion

Abstract: Alborz Mountains host Caspian Hyrcanian forest ecoregion along the northern slopes and forest steppe ecoregion in highlands. Hyrcanian forest covers the southeastern part of Caucasus biodiversity hotspot and is of great biogeographic importance. Altitudinal pattern and correlation between woody species biodiversity (DIV), forest structure ((stem density (DEN), mean basal area (MBA) and mean height class (MHC)) and disturbance (DIS) were explored along 2,400 m altitudinal gradient in Hyrcanian relict forest, Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
2
14
0
2
Order By: Relevance
“…We found that uncorrected functional diversity (FRic and Rao's Q) decreased with altitude which means that the vegetation became less functionally rich and less functionally dissimilar. This observation confirms findings of other studies who found a linear decreasing pattern in functional diversity along altitude for small mammals (e.g., Du et al, ), vascular plants (e.g., Jafari, Zarre, & Alavipanah, ; Lee, Chun, & Cho, ) or lichens (Bässler et al, ). However, functional diversity can be strongly correlated with species richness simply due to the fact that a larger species pool allows for a larger set of functional traits (Mason et al, ; Petchey et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…We found that uncorrected functional diversity (FRic and Rao's Q) decreased with altitude which means that the vegetation became less functionally rich and less functionally dissimilar. This observation confirms findings of other studies who found a linear decreasing pattern in functional diversity along altitude for small mammals (e.g., Du et al, ), vascular plants (e.g., Jafari, Zarre, & Alavipanah, ; Lee, Chun, & Cho, ) or lichens (Bässler et al, ). However, functional diversity can be strongly correlated with species richness simply due to the fact that a larger species pool allows for a larger set of functional traits (Mason et al, ; Petchey et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…In Iran, the studies related to vegetation structure as well as the flora mainly focused on forests (e.g. Jafari and Akhani 2008;Siadati et al 2010;Jafari et al 2013;Naqinezhad et al 2015;Gholizadeh et al 2017), while few studies were conducted in the regions above 2000 m (e.g. Akhani et al 2013;Mahdavi et al 2013;Noroozi et al 2011;Moradi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In order to analyze the variation in the composition of functional traits along the elevation gradient, principal coordinate analysis (PCoA -Gower 1966) was applied on a pairwise belt-to-belt dissimilarity matrix based on Gower's coefficients (because of the categorical nature of the dataset -Gower 1971) using the PAST software package (Hammer et al 2001). UPGMA clustering method using the Gower's coefficient matrix was adopted to re-test the PCoA results.…”
Section: Discussionmentioning
confidence: 99%